2000
DOI: 10.1203/00006450-200011000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Function in Sick Very Preterm Infants

Abstract: Some very preterm neonates admitted to the neonatal intensive care unit show circulatory and respiratory problems that improve after administration of steroids. It is unclear whether these symptoms could be caused by adrenal insufficiency. The objective of our study was to investigate the cortisol levels and the cortisol release from the adrenals after ACTH in very preterm infants with and without severe illness and to find whether a relation exists between adrenal function and outcome. An ACTH test (0.5 g) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 30 publications
(20 reference statements)
5
87
1
3
Order By: Relevance
“…24,25 Subsequently, numerous studies have described lower cortisol concentrations and/or lower response to ACTH in critically ill preterm infants compared with well infants, in those receiving inotropic support compared with those not, and in those presenting with respiratory distress syndrome compared with those without. [26][27][28][29][30] In addition, several authors have reported lower cortisol responses to ACTH in infants who subsequently develop bronchopulmonary dysplasia. 28,31 -34 The possible relationship between adrenal insufficiency and cardiovascular instability is of particular interest, because if this is true, glucocorticoids may be a more appropriate therapy for hypotension than vasopressors.…”
Section: Clinical Evidencementioning
confidence: 99%
“…24,25 Subsequently, numerous studies have described lower cortisol concentrations and/or lower response to ACTH in critically ill preterm infants compared with well infants, in those receiving inotropic support compared with those not, and in those presenting with respiratory distress syndrome compared with those without. [26][27][28][29][30] In addition, several authors have reported lower cortisol responses to ACTH in infants who subsequently develop bronchopulmonary dysplasia. 28,31 -34 The possible relationship between adrenal insufficiency and cardiovascular instability is of particular interest, because if this is true, glucocorticoids may be a more appropriate therapy for hypotension than vasopressors.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Most studies examining the HPA function in preterm infants during the neonatal period showed evidence of HPA downregulation, for example, lower basal cortisol levels (e.g., Grunau et al, 2005;Hingre, Gross, Hingre, Mayes, & Richman, 1994;Huysman, Hokken-Koelega, De Ridder, & Sauer, 2000;Lee, Rajagopalan, Berg, & Moshang, 1989;Ng et al, 2004;Watterberg, Gerdes, & Cook, 2001). These lower levels appear to persist to the early infancy period (Haley, Grunau, Weinberg, & Whitfield, 2004;Haley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This condition has been labeled 'transient or relative adrenal insufficiency'. 1,[3][4][5][6][7] Transient adrenal insufficiency (TAI) in the first days of life is associated with refractory hypotension, significant respiratory distress, patent ductus arteriosus and bronchopulmonary dysplasia (BPD). 1,5,[8][9][10][11] Of critical concern is that significant hypotension is associated with intraventricular hemorrhage, periventricular leukomalacia, increased mortality and later neurodevelopmental disabilities in preterm infants.…”
Section: Introductionmentioning
confidence: 99%